Jewish and Hebrew Education in Ottoman Palestine through the Lens of Transnational History - Tadmor-Shimony, Talia (Global Histories of Education, 2023)
Chapter 1. Introduction -- Chapter 2. Actors and Networks -- Chapter 3. The Educational Institutions and Pedagogical Approaches -- Chapter 4. The Portrait of the Graduate -- Chapter 5. Between Leadership and Caring -- Chapter 6. The Body as an Educational Object.